Outer and Inner Space in Craig Thompson’s Blankets: A Visual Representation Perspective (Papers in Arts and Humanities, 2023)
Written in 2003, Craig Thompson’s graphic novel Blankets manages to arouse readers’ attention through its complex emotional background that entwines the protagonist’s constant attempts to live a normal, happy life with his psychological instability, as well as his personal coming-of-age and first love with strict religious education and a detachment from his childhood memories. This paper, however, attempts to analyse the concepts of space and time from the point of view of visual representation, the author succeeding in creating the idea of temporal development through constant flashbacks, inner space representations, the novel being retrospectively narrated; at the same time, a series of artfully coined images that symbolise winter’s purity and cleanliness come to oppose the ugliness of the social context (unspoiled versus ravaged outer space) that traps the hero in an impossible universe that annihilates any outbursts of creativity, ingenuity and love.
Keywords: inner space; outer space; time; visual representation; emotional interpretation